(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As to start with the target first which means: - The current research aims to identify: The effect of a model based on Hatagogia in the achievement of students of the Department of Family Education and Artistic Professions in the subject of handicrafts. The Sample The sample of the research was determined for the students of the fourth stage of the morning study of the school year, which numbered (21) male and female students. The researcher chose the random method by (10) students to represent the control group in which the students study handicrafts in the usual way (lecture and discussion), (11) students to represent the group Experimental, whose students are exposed to the independent variable (a model based on the Hatagogia) when teaching the subject of handicrafts. Results The results of the research resulted in the superiority of the students of the experimental group who studied according to a model based on the Hatagogia, over the students of the control group who studied according to the usual method in the collection of handicrafts. Conclusions The researcher concluded the superiority of the experimental group in the post-test, after they were exposed to the Hatagoga-based educational model prepared by the researcher, which includes a set of frameworks with several skills, and these skills explain to the learner the steps in a simplified manner according to the requirements of their needs.